2017
DOI: 10.1016/j.amepre.2016.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Universal Motorcycle Helmet Laws to Reduce Injuries: A Community Guide Systematic Review

Abstract: Universal helmet laws are effective in increasing motorcycle helmet use and reducing deaths and injuries. These laws are effective for motorcyclists of all ages, including younger operators and passengers who would have already been covered by partial helmet laws. Repealing universal helmet laws decreased helmet use and increased deaths and injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 87 publications
2
27
0
1
Order By: Relevance
“…Ichiwaka et al reported a 41% reduction in head injuries in Thailand 2 years after the implementation of a mandatory helmet use law. 7 A similar reduction in head injuries and fatalities has been reported in Malaysia, 8 Vietnam, 9 USA 3 and Italy 10 after the implementation of helmet use laws. Bicycle helmet use is a means of reducing morbidity and mortality among bike users.…”
Section: Introductionsupporting
confidence: 63%
“…Ichiwaka et al reported a 41% reduction in head injuries in Thailand 2 years after the implementation of a mandatory helmet use law. 7 A similar reduction in head injuries and fatalities has been reported in Malaysia, 8 Vietnam, 9 USA 3 and Italy 10 after the implementation of helmet use laws. Bicycle helmet use is a means of reducing morbidity and mortality among bike users.…”
Section: Introductionsupporting
confidence: 63%
“…Similar arguments have previously been made for HIV prevention strategies (50) (51) and other safety devices and mandates such as motorcycle helmet laws (52) and seat-belts (53). However, research on these topics finds no such increase in adverse outcomes at the population level but rather improvements in safety and well-being, suggesting that even if risk compensation occurs in some individuals, that effect is dwarfed by the increased safety at the population level (53,54). Further, even for deliberately high-risk recreational activities such as alpine skiing and snowboarding, wearing a helmet was generally associated with risk reduction orientedbehavior (55), suggesting safety devices are both compatible with and perhaps encourage safety-oriented behavior.…”
Section: B2 Sociological Considerations and Anticipating Populationsupporting
confidence: 55%
“…A systematic review by Peng et al reported that implementing universal helmet laws in the USA increased helmet use by 47% and reduced total injuries by 32% and injuries per registered motorcycle by 29%. 26 Another study by Lee reveals that lives saved from the helmet law in the USA were estimated to be associated with an aggregated life yield value of approximately US$940 million. 27 The studies in Asia and Europe also consistently demonstrated that wearing a helmet reduces the risk of death, craniocerebral trauma and facial injuries by up to one-half.…”
Section: Discussionmentioning
confidence: 99%